Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(A=\left(3+\sqrt{5}\right)\left(\sqrt{5}-1\right)\cdot\sqrt{6-2\sqrt{5}}\)
\(=\left(3+\sqrt{5}\right)\left(6-2\sqrt{5}\right)\)
\(=18-6\sqrt{5}+6\sqrt{5}-10=8\)
b: \(B=\left(\sqrt{5}+\sqrt{3}\right)\cdot\sqrt{2}\cdot\left(\sqrt{5}-\sqrt{3}\right)\)
\(=2\left(5-3\right)=2\cdot2=4\)
\(a^3=16-8\sqrt{5}+16+8\sqrt{5}+96\sqrt[3]{\left(16-8\sqrt{5}\right)\left(16+8\sqrt{5}\right)}\)
\(a^3=32+96\sqrt[3]{-64}=32+96.\left(-4\right)=-352\)
đến đây dễ r
\(a^3=32+3\sqrt[3]{\left(16-8\sqrt{5}\right)\left(16+8\sqrt{5}\right)}\left(\sqrt[3]{16+8\sqrt{5}}+\sqrt[3]{16-8\sqrt{5}}\right)\)
a, \(5\sqrt{\left(-2\right)^4}=5\sqrt{2^4}=5.2^2=5.4=20\)
b, \(-4\sqrt{\left(-3\right)^6}=-4\sqrt{3^6}=-4.3^3=-4.27=-108\)
c,\(\sqrt{\sqrt{\left(-5\right)^8}}=\sqrt{\sqrt{5^8}}=\sqrt{5^4}=5^2=25\)
d ,\(2\sqrt{\left(-5\right)^6}+3\sqrt{\left(-2\right)^8}\)
\(=2\sqrt{5^6}+3\sqrt{2^8}\)
=\(2.5^3+3.2^4=2.125+3.16=298\)
a) \(5\sqrt{\left(-2\right)^4}\) \(=5\left|\left(-2\right)^2\right|=5.4=20\)
b) \(-4\sqrt{\left(-3\right)^6}=-4\left|\left(-3\right)^3\right|=-4.27=-108\)
c) \(\sqrt{\sqrt{\left(-5\right)^8}}=\left|\left(-5\right)^4\right|=5^4=625\)
d) \(2\sqrt{\left(-5\right)^6}+3\sqrt{\left(-2\right)^8}\) \(=2\left|\left(-5\right)^3\right|+3\left|\left(-2\right)^4\right|\)
\(=-2.\left(-125\right)+3.16\)
\(= 250 + 48 = 298\)
\(a^3=16-8\sqrt{5}+16+8\sqrt{5}+3.\sqrt[3]{16^2-8^2.5}a\)
\(a^3=32+3.\sqrt[3]{4^3\left(4-5\right)}a=32-12a\)
\(f\left(x\right)=\left[\left(32-12a\right)+12a-31\right]^{2016}=1^{2016}=1\)
a=\(\sqrt[3]{16-8\sqrt{5}}\)+\(\sqrt[3]{16+8\sqrt{5}}\)
=\(\sqrt[3]{1-3\sqrt{5}+15-5\sqrt{5}}+\sqrt[3]{1+3\sqrt{5}+15+5\sqrt{5}}\)=\(\sqrt[3]{\left(1-\sqrt{5}\right)^3}+\sqrt[3]{\left(1+\sqrt{5}\right)^3}\)
=1-\(\sqrt{5}+1+\sqrt{5}\)=2
thay vào ta được f(a)=(8+24-31)2016=(-1)2016=1
a) \(5\sqrt{\left(-2\right)^4}=5\sqrt{\left(2^2\right)^2}=5\left|4\right|=5.4=20\)
b)\(-4\sqrt{\left(-3\right)^6}=-4\sqrt{\left(3^3\right)^2}=-4\left|27\right|=-4.27=-108\)
c) \(\sqrt{\sqrt{\left(-5\right)^8}}=\sqrt{\sqrt{\left(5^4\right)^2}}=\sqrt{\left(5^2\right)^2}=25\)
d)
\(A=\sqrt{8-a}+\sqrt{5+a}\)
\(A^2=\left(\sqrt{8-a}+\sqrt{5+a}\right)^2\)
\(A^2=\left(8-a\right)+\left(5+a\right)+2\sqrt{\left(8-a\right)\left(5+a\right)}\)
\(A^2=13+2\cdot34=81\Rightarrow A=9\)
\(\left(\sqrt{8-a}+\sqrt{a+5}\right)^2=8-a+a+5+2.\sqrt{\left(8-a\right)\left(a+5\right)}=13+2.34=13+68=81\)
=>\(\sqrt{8-a}+\sqrt{a+5}=\sqrt{81}=9\)
\(1,\sqrt{\left(-0,3\right)^2}=\sqrt{0,09}=0,3\)
\(2,-\frac{1}{2}\sqrt{\left(0,3\right)^2}=-\frac{1}{2}.0,3=-0,15\)
\(3,\sqrt{a^{10}}=\sqrt{\left(a^5\right)^2}=a^5\left(a\ge0\right)\)
\(4,\sqrt{\left(2-x\right)^2}=\left|2-x\right|=2-x\left(x\le2\right)\)
\(5,\sqrt{x^2+2x+1}=\sqrt{\left(x+1\right)^2}=\left|x+1\right|\)
\(6,\sqrt{\left(1-\sqrt{2}\right)^2}=\left|1-\sqrt{2}\right|=\sqrt{2}-1\)(Vì \(1< \sqrt{2}\))
\(7,\sqrt{11+6\sqrt{2}}=\sqrt{9+6\sqrt{2}+2}=\sqrt{\left(3+\sqrt{2}\right)^2}=3+\sqrt{2}\)
\(8,\sqrt{8-2\sqrt{7}}-\sqrt{8+2\sqrt{7}}=\sqrt{7-2\sqrt{7}+1}-\sqrt{7+2\sqrt{7}+1}\)
\(=\sqrt{\left(\sqrt{7}-1\right)^2}-\sqrt{\left(\sqrt{7}+1\right)^2}\)
\(=\left(\sqrt{7}-1\right)-\left(\sqrt{7}+1\right)\)
\(=-2\)
\(9,\sqrt{6+2\sqrt{5}}+\sqrt{6-2\sqrt{5}}=\sqrt{5+2\sqrt{5}+1}+\sqrt{5-2\sqrt{5}+1}\)
\(=\sqrt{\left(\sqrt{5}+1\right)^2}+\sqrt{\left(\sqrt{5}-1\right)^2}\)
\(=\sqrt{5}+1+\sqrt{5}-1\)
\(=2\sqrt{5}\)
a: \(=\sqrt{5}+2+\sqrt{3}+1-\sqrt{5}-\sqrt{3}=3\)
b: \(=\left(-\sqrt{5}-2+\sqrt{5}-\sqrt{3}\right)\cdot\left(2\sqrt{3}+3\right)\)
\(=-\sqrt{3}\left(2+\sqrt{3}\right)\cdot\left(2+\sqrt{3}\right)\)
\(=-\sqrt{3}\left(7+4\sqrt{3}\right)=-7\sqrt{3}-12\)
c: \(=\dfrac{\sqrt{2}+\sqrt{3}+2}{\left(\sqrt{2}+\sqrt{3}+2\right)+\sqrt{2}\left(\sqrt{2}+\sqrt{3}+2\right)}=\dfrac{1}{1+\sqrt{2}}=\sqrt{2}-1\)
\(\sqrt{8-a}+\sqrt{5+a}=5\left(Đk:-5\le a\le8\right)\)
\(8-a+5+a+2\sqrt{\left(8-a\right)\left(5+a\right)}=25\)
\(\sqrt{\left(8-a\right)\left(5+a\right)}=6\)